From Melos to My Lai : war and survival - Tritle, Lawrence A., 1946- (Routledge, 2000)
Annotation From Melos to My Laipresents an erudite, provocative and moving analysis of the accounts of violence in the literature and history of ancient Greece and in the film literature and veterans' accounts of the Vietnam War. This comparative investigation examines the nature of violence, its impact on society and culture, especially as reflected from the perspective of the survivors. The survivors include not only actual combatants, but those with whom they interact: their comrades, their wives and children, families and society as a whole. From Melos to My Laiprovides a unique contribution to the study of the impact of violence on its participants and its audience which combines an examination of the artistic representations of violence and the real-life accounts of those involved in it.